Optimization of the Secondary Optical Element of a Hybrid Concentrator Photovoltaic Module Considering the Effective Absorption Wavelength Range - Woo-Lim Jeong; Kyung-Pil Kim; Jung-Hong Min; Jun-Yeob Lee; Seung-Hyun Mun; Jeong-Hwan Park; Jang-Hwan Han; Won-Kyu Park; Sewang Yoon; Dong-Seon Lee (Applied Sciences, 2020)
Hybrid concentrator photovoltaic (CPV) architectures that combine CPV modules with low-cost solar cells have the advantage of functioning well in modest direct normal irradiance (DNI) regions as well as high-DNI regions, where these architectures allow for higher performance in a limited space. For higher performance of a hybrid CPV module, we optimized the secondary optical element (SOE) using raytracing software and conducted experimental measurements that consider the effective wavelength range. Our experiments with the optimized SOE (θ = 30°, h = 15 mm) demonstrated a maximum output power on the triple-junction cell and polycrystalline silicon cell of 212.8 W/m2 and 5.14 W/m2, respectively.